Recent Writing of Lutz Rathenow: A New GDR Poetry? - Boria Sax (GDR Bulletin, 1994)
Review essay of four titles by Rathenow: Day of Wonders. Rosemary Lanning, trans. New York: North-South Books, 1992. 26 p. Oder was schwimmt da im Auge. Weilerswist: Landpresse, 1993. 22 p. Tag der Wunder. Zürich: Nord-Süd, 1992. 26 p. Und sie liebten sich heftiger denn je. Pforzheim: Hertenstein, 1993. 13 p.